Outlier or Not? The Birth Order Effects on Educational Attainment in China - Shoudeng Zhang (Sociological Science)
This study examines birth order effects in China using sibling fixed-effect models and cohort analysis. It reveals that birth order's net effect is negative when adjusting for educational expansion and gendered sibling structures. The findings resonate with Western patterns but challenge earlier positive birth order effects documented in China. Notably, gender plays a significant role, as negative birth order effects are more pronounced in females due to gender preference in fertility and parenting. These complex findings highlight the necessity to explore the mechanisms behind birth order effects amid evolving societal norms and parental behaviors. Moreover, this study contributes novel insights by disentangling macro-level trends from birth order effects and deal with bias from sibling size and sibling gender structures by introducing newly designed adjusted birth order indices.